Pengaruh Kompetensi dan Loyalitas Karyawan terhadap Promosi Jabatan pada PT KEMET Electronics Indonesia Dengan Metode SEM-PLS - Teguh Iman Santoso; Rahmat Taufik (Journal of Management, Entrepreneur and Cooperative, 2022)
The success of a company in advancing the company must not be separated from many of its resources one of which is the human resources, which is why the company should provide direction that is positive and good welfare to its employees for the achievement of organizational goals, one of them by providing opportunities career or promotion. The purpose of this study to determine the effect of the competence and loyalty of employees to promotion in PT KEMET Electronics Indonesia. The number of samples in the data analysis of this thesis using PLS-SEM (Structural Equation Modeling-Partial Least Squares) and processed with the help of a software program SmartPLS2. The test results show that the competence of positive and significant impact on the promotion, as well as employee loyalty is also positive and significant impact on the promotion.